Detection of fraudulent actions in the financial statements with particular emphasis on hotel companies - Vasilev, Dragan; Cvetković, Dragan; Grgur, Aleksandar (Hotel and Tourism Management, 2019)
Financial statements are one of the key sources of information for stakeholders of companies. Therefore, financial reporting aims at presenting an objective and transparent state of an enterprise. In order to protect the interests of all stakeholders of companies, whether external or internal, the role of financial accountants is very important, which is related to the detection of fraudulent activities in the financial statements. Forensic accountants with the knowledge they possess in the field of accounting, auditing, management and other skills, have the ability to clearly understand the irregularities and injustices that occur within the company. Fraudulent actions are most often a case of using an enterprise management strategy to gain benefits to the interests of other marketers that surround it. The aim of the paper is to show the significance of the role of a financial accountant in detecting fraudulent actions in the financial statements. The subject of this paper is to investigate the possibility of fraudulent actions and to look into the specific role forensic accountants have in this process.